Scintigraphic and echocardiographic evaluation of patients with cardiac transthyretin amyloidosis and first-degree relatives. (20th July 2021) - Holcman, K; Rubis, P; Szot, W; Graczyk, K; Stepien, A; Lesniak-Sobelga, A; Hlawaty, M; Wisniowska-Smialek, S; Dziewiecka, E; Karabinowska, A; Mroz, K; Podolec, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): Pfizer Research Grant (ID#57165999) Background: Misfolding of transthyretin (TTR) is the source of two distinct forms of amyloidosis (ATTR): acquired or wild-type (ATTRwt) and hereditary (ATTRm), which is transmitted in an autosomal dominant inheritance with a variable penetrance. Types of transthyretin (TTR) gene mutations display genetic and ethnic variability. Purpose: The aim of this prospective study was to assess the TTR gene variants, echocardiographic parameters and regional left ventricle 99mTc-DPD uptake among patients with ATTR and first-degree relatives. Methods: We present data based on evaluation of first 25 patients (13 (52%) females), including 10 (40%) index patients with ATTR (age 66.4 ± 13 years) and 15 (60%) first-degree relatives who were studied between June 2020 and February 2021. Analysis included clinical data, free light chain blood immunoglobulins and urine immunofixation, transthoracic echocardiography (TTE) with global longitudinal strain (GLS) analysis, single-photon emission computed tomography (SPECT) with 3, 3-disphono-1, 2-propanodicarboxylic acid (DPD), genetic testing by an amplicon-based next-generation TTR sequencing approach, and in selected cases cardiac or soft tissue biopsy. Results: Overall, 6 index patients were diagnosed with ATTRm and 4 with ATTRwt presenting mixed, cardiac or neuropathic phenotype. There were detected following types of TTR variants - Phe53Leu, Ala101Val, Glu112Lys, Glu109Lys. Nine out of 10 index patients were diagnosed with amyloid cardiomyopathy (CA) with grade 2-3 tracer uptake in SPECT and symptomatic heart failure (NYHA 2.2 ± 1.1; NT-proBNP value 2224 ± 2799 pg/ml). In both ATTRm and ATTRwt there were patients presenting with either focal or diffuse tracer pattern evaluated by SPECT technique. In TTE there was marked left ventricle (LV) hypertrophy with maximum wall thickness of 22 ± 5 mm and LV mass value index value of 382 ± 111 g/m2. All patients with CA had abnormal global longitudinal strain (GLS, -14.5 ± 5%) and diastolic dysfunction (EA 1.56 ± 0.76, E/E' 16 ± 11). None of relatives expressed tracer uptake in scintigraphy. Overall, 5 first-degree relatives were diagnosed with Phe53Leu variant, among them two patients presented with decreased GLS value. Conclusions: Patients with ATTR presented in TTE with LV hypertrophy, decreased GLS value, diastolic dysfunction and grade 2-3 in scintigraphy with either focal or diffuse tracer uptake in SPECT technique. None of first-degree relatives expressed increased tracer uptake in scintigraphy. However, some of relatives who were diagnosed with pathogenic TTR variant presented with decreased GLS value.